2021
DOI: 10.7759/cureus.13081
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes in Carbapenem-Resistant Enterobacteriaceae Infections Treated With Ceftazidime-Avibactam: A Single-Center Observational Study

Abstract: IntroductionAmong the several newer beta lactam+beta lactase inhibitors (BL/BLI), ceftazidime-avibactam is the only drug showing activity against OXA-48-like producers. Hence, it is being increasingly used in India to treat infections caused by carbapenem-resistant Enterobacteriaceae (CRE), especially as a colistin-sparing agent. We have used ceftazidime-avibactam in patients suspected and confirmed to have CRE infections in our center, and present a retrospective analysis of our experience. MethodsWe conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(42 citation statements)
references
References 18 publications
0
27
0
1
Order By: Relevance
“…The database search described in Database Search generated 17 eligible articles ( Sousa et al, 2018 ; Kuang et al, 2020 ; Guimarães et al, 2019 ; Rathish et al, 2021 ; Shields et al, 2018 ; Tumbarello et al, 2019 ; Ackley et al, 2020 ; Iannaccone et al, 2020 ; Castón et al, 2020 ; Tumbarello et al, 2021 ; Zhu et al, 2021 ; King et al, 2017 ; Temkin et al, 2017 ; De la Calle et al, 2019 ; Chen et al, 2020 ; Jiang et al, 2020 ; Jorgensen et al, 2020 ). Specifically, 1,106 references were found by searching for the keywords: “ceftazidime avibactam” and “carbapenem resistant.” After removing the duplicates, 667 potentially relevant articles were left.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The database search described in Database Search generated 17 eligible articles ( Sousa et al, 2018 ; Kuang et al, 2020 ; Guimarães et al, 2019 ; Rathish et al, 2021 ; Shields et al, 2018 ; Tumbarello et al, 2019 ; Ackley et al, 2020 ; Iannaccone et al, 2020 ; Castón et al, 2020 ; Tumbarello et al, 2021 ; Zhu et al, 2021 ; King et al, 2017 ; Temkin et al, 2017 ; De la Calle et al, 2019 ; Chen et al, 2020 ; Jiang et al, 2020 ; Jorgensen et al, 2020 ). Specifically, 1,106 references were found by searching for the keywords: “ceftazidime avibactam” and “carbapenem resistant.” After removing the duplicates, 667 potentially relevant articles were left.…”
Section: Resultsmentioning
confidence: 99%
“…The studies were published between 2017 and 2021. Four studies were from the USA ( King et al, 2017 ; Shields et al, 2018 ; Ackley et al, 2020 ; Jorgensen et al, 2020 ), three were from Spain ( Sousa et al, 2018 ; De la Calle et al, 2019 ; Castón et al, 2020 ), four were from China ( Chen et al, 2020 ; Jiang et al, 2020 ; Kuang et al, 2020 ; Zhu et al, 2021 ), three were from Italy ( Tumbarello et al, 2019 ; Iannaccone et al, 2020 ; Tumbarello et al, 2021 ), one was from Brazil ( Guimarães et al, 2019 ), one was from India ( Rathish et al, 2021 ), and one was from Europe and Australia ( Temkin et al, 2017 ). In terms of the pathogens, most of the studies reported carbapenem-resistant Enterobacteriaceae (CRE) with carbapenem-resistant Klebsiella pneumoniae (CKP) as the most frequent, while one study included both CKP and carbapenem-resistant Pseudomonas aeruginosa (CRPA) ( Temkin et al, 2017 ) and one study reported CRE, CRPA, and Acinetobacter baumannii (AB) ( Kuang et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 17 19 Although CZA salvage therapy for severe KPC ( Klebsiella pneumoniae carbapenemase) infections including bacteremia has been well established, its utility would be of limited import for our CRE infections. 20 …”
Section: Urrent E Videncementioning
confidence: 99%